HISTORY OF WRITING HADITH THOUGHT IN THE INDIAN REGION - Ritonga, Ade Rahmat (Nabawi: Journal of Hadith Studies, 2025)
This research examines the history of writing and the development of hadith thought in the Indian region, which has a significant role in the Islamic scientific tradition. This area has been an important center for hadith studies since the early days of Islam, with major contributions from scholars such as Shāh Walyiullāh al-Diḥlawī who is known for his deep and comprehensive thinking. This study aims to understand how the tradition of writing, disseminating and teaching hadith developed in India, as well as the factors that influenced it, both historically, socially and culturally. Through a historical approach and literature analysis, this research found that Indian scholars played an important role in preserving and developing hadith studies, including in the compilation of hadith books, developing methods of sanad and matan criticism, as well as adapting hadith thinking to local contexts. This research also explores how external factors such as the Islamic reform movement and socio-political dynamics in this region have helped shape the way scholars think about hadith. The results of this study show that the history of the writing of hadith thought in the Indian region not only contributed to the development of Islamic scientific traditions locally but also had a significant influence on Islamic studies in the global world. This study confirms the importance of the Indian region as an integral part in the scientific historiography of hadith and opens up opportunities for further studies from an interdisciplinary perspective. [Penelitian ini mengkaji sejarah penulisan dan perkembangan pemikiran hadis di kawasan India, yang memiliki peran signifikan dalam tradisi keilmuan Islam. Kawasan ini telah menjadi pusat studi hadis yang penting sejak masa awal Islam, dengan kontribusi besar dari ulama-ulama seperti Syāh Waliyullāh al-Diḥlawī yang dikenal dengan pemikirannya yang mendalam dan komprehensif. Kajian ini bertujuan untuk memahami bagaimana tradisi penulisan, penyebaran, dan pengajaran hadis berkembang di India, serta faktor-faktor yang memengaruhinya, baik secara historis, sosial, maupun budaya. Melalui pendekatan historis dan analisis literatur, penelitian ini menemukan bahwa para ulama India memainkan peran penting dalam melestarikan dan mengembangkan studi hadis, termasuk dalam penyusunan kitab-kitab hadis, pengembangan metode kritik sanad dan matan, serta adaptasi pemikiran hadis dengan konteks lokal. Penelitian ini juga mengeksplorasi bagaimana faktor eksternal seperti gerakan reformasi Islam dan dinamika sosial-politik di kawasan ini turut membentuk corak pemikiran ulama terhadap hadis. Hasil kajian ini menunjukkan bahwa sejarah penulisan pemikiran hadis di kawasan India tidak hanya berkontribusi pada pengembangan tradisi keilmuan Islam secara lokal, tetapi juga memberikan pengaruh signifikan pada studi Islam di dunia global. Studi ini menegaskan pentingnya kawasan India sebagai bagian integral dalam historiografi keilmuan hadis dan membuka peluang untuk kajian lanjutan dalam perspektif lintas disiplin.]